2017
DOI: 10.1289/ehp1545
|View full text |Cite|
|
Sign up to set email alerts
|

Associations between Ambient Fine Particulate Oxidative Potential and Cardiorespiratory Emergency Department Visits

Abstract: Background:Oxidative potential (OP) has been proposed as a measure of toxicity of ambient particulate matter (PM).Objectives:Our goal was to address an important research gap by using daily OP measurements to conduct population-level analysis of the health effects of measured ambient OP.Methods:A semi-automated dithiothreitol (DTT) analytical system was used to measure daily average OP (OPDTT) in water-soluble fine PM at a central monitor site in Atlanta, Georgia, over eight sampling periods (a total of 196 d)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(101 citation statements)
references
References 70 publications
4
97
0
Order By: Relevance
“…One reason for this could be that aerosol acidity influences solubilization and the concentrations of toxic forms of trace species, such as transition and heavy metals, that have been linked to negative health effects (Kelly and Fussell, 2012;Lippmann, 2014;Rohr and Wyzga, 2012;Chen and Lippmann, 2009;Frampton et al, 1999). Transition metal ions (TMIs), such as soluble Cu and Fe from acid dissolution, contribute significantly to the oxidative potential of particles Pöschl and Shiraiwa, 2015), which has been linked to cardiorespiratory emergency department visits with a stronger association than PM 2.5 mass (Abrams et al, 2017;Bates et al, 2015). Ye et al (2018) report a strong association between soluble Fe, which is modulated by particle acidity and aerosol water content, and cardiovascular endpoints.…”
Section: The Importance Of Atmospheric Aciditymentioning
confidence: 99%
See 2 more Smart Citations
“…One reason for this could be that aerosol acidity influences solubilization and the concentrations of toxic forms of trace species, such as transition and heavy metals, that have been linked to negative health effects (Kelly and Fussell, 2012;Lippmann, 2014;Rohr and Wyzga, 2012;Chen and Lippmann, 2009;Frampton et al, 1999). Transition metal ions (TMIs), such as soluble Cu and Fe from acid dissolution, contribute significantly to the oxidative potential of particles Pöschl and Shiraiwa, 2015), which has been linked to cardiorespiratory emergency department visits with a stronger association than PM 2.5 mass (Abrams et al, 2017;Bates et al, 2015). Ye et al (2018) report a strong association between soluble Fe, which is modulated by particle acidity and aerosol water content, and cardiovascular endpoints.…”
Section: The Importance Of Atmospheric Aciditymentioning
confidence: 99%
“…The bisulfate anion is often more abundant than the sulfate ion in fine particles; however, TSO 4 is often conceptualized has having an effective charge of negative 2. Adams et al, 1999) has been suggested, defined as…”
Section: Proxies Based On Electroneutralitymentioning
confidence: 99%
See 1 more Smart Citation
“…The AA assays would be more specific to the oxidative potential of transition metals (Godri et al, 2011;Yang et al, 2014), but ascorbic acid is known to react with organics such as quinones (Shang et al, 2012;Visentin et al, 2016). All of these assays have shown some correlations with health outcomes in epidemiological studies (Abrams et al, 2017;Bates et al, 2015;Fang et al, 2016;Strak et al, 2017;Weichenthal et al, 2016a, b;Yang et al, 2016). Detailed PM 10 characterization was performed in parallel, by analyzing up to 130 chemical species that incorporated a broad array of organic species and trace elements (Chevrier, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the oxidative potential (OP) of particulate matter (PM) has been proposed as a biologically relevant metric to be associated with a number of health endpoints and biomarkers of toxic effects in humans [1][2][3][4][5][6][7]. It is based on the increasing consensus that the oxidative stress is an important mechanism of human toxicity related to exposure to atmospheric aerosols.…”
Section: Introductionmentioning
confidence: 99%